2018
DOI: 10.1029/2018jb015676
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Onset of Strain Localization Within Anisotropic Shale Using Digital Volume Correlation of Time‐Resolved X‐Ray Microtomography Images

Abstract: Digital volume correlation analysis of time‐resolved X‐ray microtomography scans acquired during in situ triaxial compression of Green River shale cores provided time series of 3‐D incremental strain fields that elucidated evolving deformation processes by quantifying microscopic strain localization. With these data, we investigated the impact of mechanical anisotropy on microscopic strain localization culminating in macroscopic shear failure. We conducted triaxial compression experiments with the maximum comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 47 publications
10
58
0
Order By: Relevance
“…Tracking the 2D strain field on the surface of Carrara marble loaded in uniaxial compression also reveals the dominance of shear and dilatational strain events throughout loading, with a greater frequency of dilatational events near macroscopic failure (Tal et al, 2016). DVC analyses on laminated Green River shale (McBeck et al, 2018) provide a different partitioning of the strain modes than observed in the experiments on marble, sandstone and basalt. In two experiments on shale, the magnitude of radial dilation was of the same order as the magnitude of axial contraction throughout loading .…”
Section: Brittle Failure Processes In Rocksmentioning
confidence: 83%
“…Tracking the 2D strain field on the surface of Carrara marble loaded in uniaxial compression also reveals the dominance of shear and dilatational strain events throughout loading, with a greater frequency of dilatational events near macroscopic failure (Tal et al, 2016). DVC analyses on laminated Green River shale (McBeck et al, 2018) provide a different partitioning of the strain modes than observed in the experiments on marble, sandstone and basalt. In two experiments on shale, the magnitude of radial dilation was of the same order as the magnitude of axial contraction throughout loading .…”
Section: Brittle Failure Processes In Rocksmentioning
confidence: 83%
“…We tracked the positive and negative divergence and curl in order to capture the dilation, contraction, and right‐lateral and left‐lateral shear strain (Text S1 in the supporting information). Following previous approaches to DVC analysis (McBeck et al, ), we calculated incremental displacement fields between 10 tomogram pairs that are separated by approximately constant changes in applied axial strain, εzzM. To account for small differences in εzzM between each pair, we normalized the calculated divergence and curl values by εzzM.…”
Section: Methodsmentioning
confidence: 99%
“…Following the approach of McBeck et al () and Renard et al (), we performed DVC analysis to obtain information on the evolution of the displacement field within the serpentinite (Figure ). Three‐dimensional DVC analysis was first developed for engineering applications (Bay et al, ) and then applied to study of soils (Viggiani et al, ) and sandstones (Louis et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Following McBeck et al (), we report changes in the local volumetric and shear strain fields using the first invariant of the incremental strain tensor, I 1 , and the von Mises yield criterion equivalent strain, (3 J 2 ) 1/2 , where J 2 is the second invariant of the incremental strain deviator tensor, J2=13I12I2, and I 1 and I 2 are the first and second invariants of the incremental strain tensor, respectively. In the adopted sign convention, negative values of I 1 indicate net volumetric dilatancy, positive values of I 1 indicate net volumetric contraction, and (3 J 2 ) 1/2 is used as a proxy for the magnitude of incremental shear strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation